2020
DOI: 10.1111/jgh.15109
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband imaging with near‐focus magnification for discriminating the gastric tumor margin before endoscopic resection: A prospective randomized multicenter trial

Abstract: Background and Aim This study investigated the usefulness of near‐focus narrowband imaging (NF‐NBI) for determining gastric tumor margins compared with indigo carmine chromoendoscopy (ICC) before endoscopic submucosal dissection (ESD). Methods This prospective randomized controlled trial was conducted at seven teaching hospitals in Korea. Patients with gastric adenoma or differentiated adenocarcinoma undergoing ESD were enrolled and randomly assigned to the NF‐NBI or ICC group. A marking dot was placed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…We assume that the shorted time needed to focus on the lesion is a result of the simple procedure of one-step button for NF-NBI. The usefulness of NF-NBI has been reported in the pharynx, esophagus [12,13] and colon [14,15], however there is only one study in the stomach that assessed the delineation accuracy of EGC margin using NF-NBI [16]. There has been no study that prospectively assessed the diagnostic performance of NF-NBI for newly detected lesions during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assume that the shorted time needed to focus on the lesion is a result of the simple procedure of one-step button for NF-NBI. The usefulness of NF-NBI has been reported in the pharynx, esophagus [12,13] and colon [14,15], however there is only one study in the stomach that assessed the delineation accuracy of EGC margin using NF-NBI [16]. There has been no study that prospectively assessed the diagnostic performance of NF-NBI for newly detected lesions during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only evaluated whether the target lesion was cancerous or noncancerous. To evaluate whether NF-NBI is useful for diagnosing the extent of cancerous areas, a recent prospective study reported that the delineation accuracy rate was 84.5% for EGC margin using NF-NBI before endoscopic resection [16]. Thirdly, our study included only high-risk patients of GC with a history or presence of esophageal or gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the progression of gastric-related diseases, microscopic features of the stomach mucosa such as venules, capillary network, and the shape and size of gastric fossa and recess have been structurally changed. For the first time, two studies used the NF-NBI mode in the stomach for the evaluation of a tumor lesion and its margin[ 16 , 17 ]. The role of the NF-NBI mode has been assessed recently for atrophic gastritis, according to the Kimura-Takemoto classification and intestinal metaplasia (tubular/granular GP pattern of the corpus)[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that NF-NBI successfully replaced ME-NBI in the detection of pathological lesions in the esophagus and pharynx as well as the identification of celiac disease[ 12 - 15 ]. Recent studies reported the ability of the NF-NBI mode for the detection of early gastric cancer lesions[ 16 , 17 ]. Two recently published studies considered NF endoscopy in the evaluation of gastric atrophy, intestinal metaplasia, and H. pylori infection[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%